Vietnam's Development Success Story and the Unfinished SDG Agenda - Baum, Anja (IMF Working Papers; Working Paper ;, 2020)
Despite starting as one of the poorest countries in the mid-1980s, Vietnam has achieved rapid developmental progress, reaching lower middle-income status in 2010. In line with rapid economic growth, Vietnam has achieved impressive progress towards the Sustainable Development Goals (SDGs) during this time. This paper sheds light on some elements of Vietnam's success story, highlighting crucial policies in education and electricity sectors. It undertakes a forward-looking costing exercise that focusses on five sectors - education, health, roads, water, and electricity infrastructure. Achieving the remaining SDGs in Vietnam will be a challenge, with total annual additional spending needs in the 5 subsectors estimated at 7 percent of GDP by 2030.